Pengenalan Perdagangan Saham Bagi Mahasiswa Di Kecamatan Semarang Barat - Adji Seputro; Andreas Tigor Oktaga; Gede Mandirta Tama; Made Konny Koswara; Nyoman Sri Padmini; Ida Ayu Gede Danika Esa Pradnyani (Jurnal Pengabdian kepada Masyarakat STIE AKA Semarang, 2025)
This Community Service Program (PkM) aims to introduce the fundamentals and practices of stock trading to university students in Semarang Barat District. The program was conducted in collaboration with the Indonesia Stock Exchange Representative Office of Central Java 1. The methods included educational sessions, stock trading simulations, and interactive discussions. The results indicate an increased understanding among students regarding capital market mechanisms, investment instruments, and potential risks in stock trading. Furthermore, the program encouraged a mindset shift: students who initially perceived stocks as complex and high-risk instruments came to recognize the capital market as a transparent, legal, and accessible investment avenue. Theoretically, this activity aligns with literature highlighting the critical role of financial literacy and capital market education in shaping young investors’ behavior.